2002
DOI: 10.1128/aem.68.9.4546-4553.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Properties and Intracellular Localization of the Novel Trichoderma reesei β-Glucosidase BGLII (Cel1A)

Abstract: This paper describes the characterization of an intracellular ␤-glucosidase enzyme BGLII (Cel1a) and its gene (bgl2) from the cellulolytic fungus Trichoderma reesei (Hypocrea jecorina). The expression pattern of bgl2 is similar to that of other cellulase genes known from this fungus, and the gene would appear to be under the control of carbon catabolite repression mediated by the cre1 gene. The BGLII protein was produced in Escherichia coli, and its enzymatic properties were analyzed. It was shown to be a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 39 publications
6
99
0
1
Order By: Relevance
“…13 A number of transcriptomic studies have shown that orthologs of these transporters are transcriptionally upregulated in response to plant cell wall material or cellobiose in diverse fungi, suggesting they are fundamental to the strategies used by fungi to interact with plants. [14][15][16] The identification of these genes confirmed reports of cellodextrin permeases 17 and intracellular β-glucosidases 18 in T. reesei. The importance of these transporters to biomass degradation by N. crassa and other fungi inspired us to engineer Figure 1.…”
supporting
confidence: 82%
“…13 A number of transcriptomic studies have shown that orthologs of these transporters are transcriptionally upregulated in response to plant cell wall material or cellobiose in diverse fungi, suggesting they are fundamental to the strategies used by fungi to interact with plants. [14][15][16] The identification of these genes confirmed reports of cellodextrin permeases 17 and intracellular β-glucosidases 18 in T. reesei. The importance of these transporters to biomass degradation by N. crassa and other fungi inspired us to engineer Figure 1.…”
supporting
confidence: 82%
“…52). Barnett et al (15) have shown and Takashima et al (16) have suggested roles for bgl1/cel3a and bgl2/cel1a, respectively, in cellulose saccharification, although BGLII/Cel1a was later shown to be an intracellular rather than a secreted protein (53). In accordance with this function, bgl1/cel3a and bgl2/cel1a expression were well correlated with the induction, by both sophorose and lactose, of other genes central to cellulose degradation.…”
Section: Figmentioning
confidence: 84%
“…P. purpurogenum was found to produce intracellular ß-glucosidase. Trichoderma reesei has also been reported to be the producer of intracellular ß-glucosidase (19).…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria like Bretlanomyces bruxellensis (11), Oenococcus oeni (11) and Clostridium thermocellum (7), the fungi like Aspergillus oryzae (16), Fusarium oxysporum (2), Trichoderma reesei (19), and the yeasts like Candida peltata (18), Candida curvata (20) are also reported to be the main producers. Penicillium purpurogenum is among the few fungi, which produced intracellular ß-glucosidase.…”
Section: Introductionmentioning
confidence: 99%